A Diverse Micromorphology of Photonic Crystal Chips for Multianalyte Sensing. Issue 12 (3rd March 2021) - Huang, Yu; Liu, Lingxiao; Yang, Xian; Zhang, Xiaoyu; Yan, Bing; Wu, Lei; Feng, Pengju; Lou, Xiaoding; Xia, Fan; Song, Yanlin; Li, Fengyu
Abstract: The diversity by nano/microstructural material or device constructing can provide the exciting opportunity for sensitivity and selectivity to achieve facile and efficient multianalyte recognition for clinical diagnosis, environment monitoring, etc., in complex system analysis. Colloidal poly(styrene–methyl methacrylate–acrylic acid) (poly(St–MMA–AA)) nanoparticle‐assembled photonic crystals (PCs) can achieve manipulative 3D structural colors and approach PC sensor chip for high‐efficient multianalysis utilizing simple dye. Focusing on the morphology effects of structural color, a PC microchip is designed and constructed with various geometrical micromorphologies. Based on the angle dependence of colloidal‐crystal structural color, the stopband distribution is explored on various morphological PC pixels. Selective fluorescent enhancement is realized for stopband‐matched PCs, which approach the successful discrimination of metal ions and complex multianalysis of groundwater. Meanwhile, printed droplet‐shaping manipulation can achieve a large‐scale structural‐color sensor array of chips with designable nano/microstructures via colloidal assembly. It will be the critical puzzle piece between macromorphology and microstructure for the structural‐color researches. Abstract : A photonic crystal microchip with geometrical micromorphologies is designed and constructed via colloidal nanoparticles assembly. Based on the angle‐dependent structural color, the stopband distribution on various morphologies of photonic crystal (PC) pixels is explored. Different geometrical micromorphologies contribute discriminative and quantitative fluorescent enhancement, which leads to the successful complex multianalysis of mining groundwater.